Analysis of the effectiveness of the training system of future computer profile specialists for the application of digital technologies - Olha Potapchuk (Kazimierz Wielki University, 2024)
The purpose of the article is to verify and justify the effectiveness of implementing an authorial system for preparing future computer professionals to apply digital technologies. The methodological basis of the publication is methods of scientific analysis, pedagogical positions on the issues of preparing future computer professionals, implementation of an authorial system for preparing future computer professionals for the application of digital technologies. The scientific novelty lies in highlighting the main results of the pedagogical experiment, which aimed to verify the effectiveness of the system for preparing future computer professionals for the application of digital technologies. The pedagogical experiment was conducted in accordance with the main stages (diagnostic, formative, control), during each of which a series of tasks and research were carried out. The research hypothesis assumes that the quality of preparation of future computer professionals for the application of ICT in professional activities will improve by implementing organizational and pedagogical conditions, principles, approaches, content, forms, and methods laid down in the authorial system for preparing future computer professionals for the application of ICT. To substantiate the conclusions regarding the effectiveness of the content and methodology of the pedagogical experiment, statistical processing of the obtained data will be conducted. It was found that EG students demonstrated significantly higher knowledge and skills in mastering and using modern ICT tools and instruments: 3D modeling technologies, including for graphic reconstruction; additive technologies; development of adaptive web resources; development and application of virtual and augmented reality applications; use of Smart technologies in education, and so on. Conclusions. Summarizing the research results, we believe that the authorial system for preparing future computer professionals for the application of ICT in professional activities is effective and positively influences the formation of their readiness for professional activities in general.